When you see it coming: stressor anticipation modulates stress effects on negative affect - Neubauer, Andreas B.; Smyth, Joshua M.; Sliwinski, Martin J. (Emotion, 2018)
Research on the effect of exposure to minor stressors in people’s daily lives consistently reports negative effects on indicators of well-being, often coined stress reactivity. Recent advances in the intensity of data collection have brought about an increasing interest in within-day associations of stress exposure and indicators of well-being, including dynamic aspects of the stress response such as stress recovery. In the present work, we investigated the other end of the stress response: the anticipation of a stressor. We hypothesized that anticipation of an upcoming stressor would be accompanied by higher negative affect. Based on the anticipatory coping account, lower negative affect after occurrence of anticipated (vs. not anticipated) stressors was predicted. We approached this question with a measurement burst study that allowed us to disentangle variation in stress processes across different time scales. One-hundred and seventy-five participants (mean age = 50, range 20-79) completed up to 3 measurement bursts. Each burst consisted of an ecological momentary assessment with 5 assessments per day over 7 days. In line with our expectations, negative affect was significantly higher after stressor anticipation, especially on days with high levels of intrusive thoughts. However, negative affect was not lower after anticipated (vs. not anticipated) stressors. Findings point to the role of perseverative cognition in the effect of stressor anticipation. Directions for future research including the role of controllability and effects on stress recovery are outlined.